Conditions Associated with Essential Tremor in Veterans: A Potential Role for Chronic Stress. (17th May 2018) - Handforth, Adrian; Parker, Gail A.
Background: Increased depression, hearing loss, dementia, alcoholism, and mortality in essential tremor patients remain unexplained. We investigated whether conditions associated with tremor are linked to chronic stress. Methods: The FY2013 Veterans Affairs database was queried for 38 selected dual diagnosis combinations in 5, 854, 223 veterans aged 21–95 years. Results: Post-traumatic stress disorder, anxiety, and depression were the most common psychiatric diagnoses in tremor patients, with the odds ratio exceeding 2 in all 15-year cohorts. Depending on age, patients with essential tremor were more likely than those without to have obsessive–compulsive disorder, bipolar illness, schizophrenia, use tobacco and abuse alcohol, have hypertension, obesity, hyperlipidemia, diabetes, vitamin D deficiency, coronary and cerebrovascular diseases, congestive heart failure, stroke, asthma, hypothyroidism, irritable bowel syndrome, renal insufficiency, alcoholic liver disease, hearing loss, glaucoma, macular degeneration, migraine, epilepsy, idiopathic polyneuropathy, history of head trauma, and 'Alzheimer's dementia. In contrast, lung and colorectal cancer, amyotrophic lateral sclerosis, psychostimulant abuse, and rheumatoid arthritis were not more common. Discussion: Post-traumatic stress disorder, anxiety, and depression, strongly associated with essential tremor, are known risk factors for poor health habits, tobacco use and alcohol abuse; collectively these are risk factors for vascular disease, with further negative health consequences for multiple organ systems. As essential tremor is associated with all these conditions, we propose that chronic stress is not only responsible for the conditions associated with tremor but in some cases itself directly and indirectly induces essential tremor, so that tremor and poor health share a common cause.